Herpes Simplex Virus-Type1 (HSV-1) Impairs DNA Repair in Cortical Neurons - De Chiara, Giovanna; Racaniello, Mauro; Mollinari, Cristiana; Marcocci, Maria Elena; Aversa, Giorgia; Cardinale, Alessio; Giovanetti, Anna; Garaci, Enrico; Palamara, Anna Teresa; Merlo, Daniela (Frontiers in Aging Neuroscience, 2016)
Several findings suggest that HSV-1 infection plays a role in the neurodegenerative processes that characterize Alzheimer’s disease, but the underlying mechanisms have yet to be fully elucidated. Here we show that HSV-1 productive infection in cortical neurons causes the accumulation of DNA lesions that include both single (SSBs) and double strand breaks (DSBs), which are reported to be implicated in the neuronal loss observed in neurodegenerative diseases. We demonstrate that HSV-1 downregulates the expression level of Ku80, one of the main components of non-homologous end joining (NHEJ), a major pathway for the repair of DSBs. We also provide data suggesting that HSV-1 drives Ku80 for proteasomal degradation and impairs NHEJ activity, leading to DSB accumulation. Since HSV-1 usually causes life-long recurrent infections, it is possible to speculate that cumulating damages, including those occurring on DNA, may contribute to virus induced neurotoxicity and neurodegeneration, further suggesting HSV-1 as a risk factor for neurodegenerative conditions.